Issues of Legal Forms of the Mediated Implementation of the Right of Public Property and Self-financing - Kulikova, Anna A. (International Review of Management and Marketing, 2016)
The article considers the nature of the relationship mediating the right of public ownership. The author studies the legal status of a public enterprise, its place in the system of legal forms of indirect realization of the right of state and municipal property. Depending on the type of property rights pertaining to the interrelation of state and municipal property the unitary enterprises are divided into types: based on the principle of operational management and based on the principle of economic management. The article critically examines the question of the necessity of the right of economic management, because of the wide scope of rights of the enterprises towards public ownership. Also attempted to define criteria for distinguishing between the scope and functional purpose under consideration of limited real rights in the sphere of state and municipal sectors of the economy. According to the results of the study conclusions are formulated about the absence of objective necessity of the existence of legal reality in two types of unitary enterprises due to lack of legal regulation of the essential differences of their tasks. The author proved that the legal form of corporations is not suitable for public property rights in those areas where the foreground is implementation of public interests but not a profit making. Keywords: legal forms, right of public property, self-financing, public ownership, property rights JEL Classifications: D23, H82, K11